Hospital food service strategies to improve food intakes among inpatients: a systematic review - Osman, Noor Suzana; Md Nor, Norazmir; Md Sharif, Mohd Shazali; Abdul Hamid, Syahrul Bariah; Rahamat, Syafiqah (Multidisciplinary Digital Publishing Institute, 2021)
This review aims to identify hospital food service strategies to improve food consumption among hospitalized patients. A systematic search that met the inclusion and exclusion criteria was manually conducted through Web of Science and Scopus by an author, and the ambiguities were clarified by two senior authors. The quality assessment was separately conducted by two authors, and the ambiguities were clarified with all the involved authors. Qualitative synthesis was used to analyze and summarized the findings. A total of 2432 articles were identified by searching the databases, and 36 studies were included. The majority of the studies applied menu modifications and meal composition interventions (n = 12, 33.3%), or included the implementation of the new food service system (n = 8, 22.2%), protected mealtimes, mealtime assistance and environmental intervention (n = 7, 19.4%), and attractive meal presentation (n = 3, 8.3%). Previous studies that used multidisciplinary approaches reported a significant improvement in food intake, nutritional status, patient satisfaction and quality of life (n = 6, 16.7%). In conclusion, it is suggested that healthcare institutions consider applying one or more of the listed intervention strategies to enhance their foodservice operation in the future.